Hydrophobic structure of hairpin ten-ring pyrrole-imidazole polyamides enhances tumor tissue accumulation/retention in vivo. Issue 9 (15th May 2018) - Inoue, Takahiro; Shimozato, Osamu; Matsuo, Nina; Mori, Yusuke; Shinozaki, Yoshinao; Lin, Jason; Watanabe, Takayoshi; Takatori, Atsushi; Koshikawa, Nobuko; Ozaki, Toshinori; Nagase, Hiroki
Graphical abstract: Highlights: The number of imidazole units of PI polyamide reflects its hydrophobicity. More hydrophobic PI polyamide preferentially retained in tumor tissues in vivo . Hydrophilic level of PI polyamide may affect its distribution and excretion in vivo . Abstract: To examine the hydrophobic structure of PI polyamides on tumor accumulation in vivo, PI polyamide-fluorescein conjugates1 –5 with the distinct number of N -methylimidazole (Im) units were synthesized. There existed an inverse relationship between the Im unit number of the compounds and their hydrophobicity. Compound1 with one Im unit and3 with three Im units accumulated and retained preferentially in tumor tissues compared to5 with five Im units. These results suggest the importance of a PI polyamide's primary structure, which partly contributes to its hydrophobic property, on its accumulation and/or retention in tumor tissues in vivo .